Realising sustainable develoment goals via organisational mental health work plan: resource-based view perspective / Prof. Dr. Corina Joseph, Nur Izyan Ismail and Siti Aimi Yasin - Joseph, Corina; Ismail, Nur Izyan; Yasin, Siti Aimi (Universiti Teknologi MARA, Kedah, 2023)
The Covid-19 outbreak not only hit the world economy but also negatively impacted people’s mental health as Covid- 19 became a foundation of intense stress for the entire global population. The first objective of this paper is to review the latest strategies related to promoting mental health work plans to stay relevant in this uncertain environment. The second objective is to suggest the importance of an organisational mental health work plan as the organisational capability using the Resource-based View Theory to sustain competitive advantage. This paper recommends several actions that promote the implementation of an organisational mental health work plan i.e. 1) empathetic leadership; 2) proper communication; 3) moral or psychological support; and, 4) promote mental health awareness. This is among the first paper that conceptualises the organisational mental health work plan as the organisational capability. This paper also proposes a hierarchical model of the mental health work plan for the business, national, and sustainable development goals.